Analisis Tinjauan Kearifan Lokal terhadap Kejadian Perambahan di Suaka Margasatwa Kateri (Studi kasus: Desa Wehali Kecamatan Malaka Tengah Kabupaten Malaka Provinsi Nusa Tenggara Timur - Yasintha Serlina Seran; Ludji Michael Riwu Kaho; Norman P. L. B. Riwu Kaho; Muhamad Soimin (Wana Lestari, 2026)
The conservation forest area of the Kateri Wildlife Sanctuary has experienced forest damage. This forest destruction is caused by forest encroachment carried out by irresponsible parties. The impact of forest destruction has implications for various environmental components and ecosystems and habitats. Local wisdom is used by the community as a guideline for attitudes and behaviors in interacting with nature and its environment. This study aims to find out whether the Local Wisdom of Wehali Village contributes to the reduction of the rate of forest destruction that occurs in the forest area of the Kateri Wildlife Sanctuary which was carried out in April-May 2024 at the Kateri Wildlife Sanctuary (Wehali Village, Central Malaka District, Malaka Regency). The method used is a survey with interviews with respondents using questionnaires and direct observations, then the data is processed using a qualitative descriptive method. The results of the study show that forest encroachment that occurs in the Kateri Wildlife Sanctuary forest area of Wehali Village are the encroachment of areas for settlements, plantations, illegal logging, and fires. The encroachment activities are carried out by immigrant communities and local communities whose live around the area due to the low social and economic eonditions, urgent demands for household economic concerns, social jealousy of local residents towards immigrant populations so that irresponsible parties use them to destroy forests. The local wisdom of Wehali Village is in the form of knowledge, including in the form of Titen science, values, ethics and morals, norms consisting of recommendations, prohibitions, and sanctions, as well as expressions. This local wisdom are used and applied as a guideline for attitudes and behaviors in preserving forests, in various physical and ritual activities, routine and incidental. However, local wisdom in Wehali Village has decreased due to deforestation that occurred in the Kateri Wildlife Sanctuary against forest conservation due to human activities that do not comply with customary rules and encroachment.